A semiselective agar medium for the identification and isolation of (Xanthomonas campestris pv. vesicatoria) from tomato and pepper seeds. - Sijam, K.; Chang, C. J.; Gitaitis, R. D. (1990)
A semiselective agar medium was developed for the identification and isolation of Xanthomonas campestris pv. vesicatoria,the causal agent of bacterial spot of pepper and tomato. The new medium,designated as CKTM,contained pourite,soy peptone,bacto tryptone,dextrose,L-glutamine,L-histidine, ammonium phosphate,potassium phosphate,magnesium sulfate,calcium chloride,and agar. Selectivity was afforded through the use of cycloheximide,bacitracin,neomycin,cephalexin,5-fluorouracil,tobramycin and tween 80. All strains of X.c. pv. vesicatoria could easily be distinguished from other pathovars of X. campestris by the formation of clear ring around their colonies,1-2 days after colony transfer or 3-4 days after dilution spread on CKTM. The clear ring usually followed by the formation of minute tan to white crystals of various intensity,depending on X.c. pv. vesicatoria strains. Detection of X.c. pv. vesicatoria was positive on 15 of 22 tomato seed lots tested,and none was detected on pepper seeds. Recovery of X.c. pv. vesicatoria ranged from 17.7 to 100% on CKTM,while 6.3 to 44.4% on Tween B medium. CKTM medium was qualitatively and quantitatively superior than Tween B medium. Reduction of contamination microflora was also achieved.